Clay Nanoparticles Composite Membranes Prepared with Three Different Polymers: Performance Evaluation - Rodrigues, Raphael; Morihama, Ana Carolina Daniel; Barbosa, Izabela Major; Leocádio, Gracyelly Nuves; Mierzwa, José Carlos (Journal of Membrane and Separation Technology, 2018)
This paper presents the results obtained from the evaluation of clay nanoparticles as an additive for improving the characteristics and performance of composite membranes cast with polysulfone (PS), polyethersulfone (PES), and polyvinylidene fluoride (PVDF). Different concentrations of clay nanoparticles, ranging from 1 to 10% based on the polymer mass, were used to prepare all dope solutions. The addition of clay nanoparticles changed the internal pore morphology of membranes, which resulted in significant changes on their performance, regarding its water permeability, and fouling potential. The optimum nanoclay concentration for permeability enhancement was different for each polymer, 1.5%, 2.0%, and 6.0% for PS, PES, and PVDF, respectively. This difference can be attributed to the differences of polymer’s hydrophobicity, based on the contact angle of a sessile water drop, which is higher for PVDF (PVDF is more hydrophobic than PS and PES). The flow improvement changed based on the main polymer. Significant changes in internal pore structure were observed for all membranes. The proportion of macrovoids was decreased and pores had a better connectivity across the cross section for PES and PS membranes. For PVDF membranes, the addition of nanoclay had a different effect on their microstructure. In this case, internal pores were 20% wider, factor that increased the average membrane porosity. The simultaneous evaluation of the clay nanoparticles used as an additive have clearly demonstrated its potential application for composite membrane production. It is also worth to note that the best way for identifying and evaluating the potential for an additive for membrane casting is considering its effects for different polymers, under the same casting conditions.